2019
DOI: 10.1111/ejn.14305
|View full text |Cite
|
Sign up to set email alerts
|

Insular resting state functional connectivity is associated with gut microbiota diversity

Abstract: The gut microbiota has recently gained attention as a possible modulator of brain activity. A number of reports suggest that the microbiota may be associated with neuropsychiatric conditions such as major depressive disorder, autism and anxiety. The gut microbiota is thought to influence the brain via vagus nerve signalling, among other possible mechanisms. The insula processes and integrates these vagal signals. To determine if microbiota diversity and structure modulate brain activity, we collected faecal sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 38 publications
2
57
0
1
Order By: Relevance
“…Previous work showed a link between gut microbiota and restingstate functional connectivity, as assessed here (9,49). Interestingly, in one study assessing bivariate relationships, Prevotella and Bacteroides were associated with insular connectivity (8). The insula has not only been discussed as part of the salience network, but also as an important component of the general task positive network (50,51).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous work showed a link between gut microbiota and restingstate functional connectivity, as assessed here (9,49). Interestingly, in one study assessing bivariate relationships, Prevotella and Bacteroides were associated with insular connectivity (8). The insula has not only been discussed as part of the salience network, but also as an important component of the general task positive network (50,51).…”
Section: Discussionmentioning
confidence: 89%
“…A few studies did assess the relation between gut microbiome composition and intrinsic brain connectivity. One resting state fMRI study (n=30), which included a subgroup of smokers, focused on the association of gut microbiota composition with insula connectivity and found its connection to several brain regions, such as occipital and lingual gyrus, frontal pole and cerebellar regions, to be associated with microbiota diversity and structure (8). Other exploratory region-of-interest (ROI) analyses did not reveal significant associations.…”
Section: Introductionmentioning
confidence: 99%
“…Past small sample studies have established the associations of gut microbiota diversity and structure with cerebellar structure and functional connectivity [32,33], highlighting the pivotal role of the cerebellum in the microbiota-gut-brain axis. Complementing and extending these previous ndings, our large sample study further revealed that higher gut microbial diversity was associated with higher GMV in Cbe in males rather than females.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gao et al reported that gut alpha diversity was associated with functional connectivity between the amygdala and thalamus, between the anterior cingulate cortex and anterior insula, and between the supplementary motor area and inferior parietal lobule in infants [48]. Curtis et al showed that insular resting-state functional connectivity was related to gut microbiota diversity [33]. Simpson and colleagues found that microbiome depletion by antibiotics resulted in altered functional connectivity among brain regions [49].…”
Section: Discussionmentioning
confidence: 99%
“…New and exciting horizons to be explored include the contribution of peripheral measures, such as gut microbiota diversity, to brain function in substance abuse and drug addiction. Here, resting‐state functional connectivity between the insula and several other brain regions was associated with bacterial microbiota diversity and structure as potentially modulated by tobacco smoking, providing a potentially novel therapeutic target for modulating brain connectivity (Curtis et al ., ).…”
Section: Human Studiesmentioning
confidence: 97%